Heteromerous Bistricyclic Aromatic Enes: Dynamic Stereochemistry of Xanthylidene‐Anthrones. Issue 12 (1st October 2015) - Suissa, M. Rachel; Cohen, Shmuel; Pogodin, Sergey; Agranat, Israel
Abstract: The heteromerous bistricyclic aromatic ene (BAE) 2, 2'‐dimethyl‐10‐(9 H ‐xanthylidene)‐9(10 H )‐anthrone (DMXA) was synthesized by a condensation of 10, 10‐dichloro‐2‐methylxanthene with 2‐methylanthrone. X‐ray crystallography of ( E )‐DMXA and xanthylidene‐anthrone (XA) indicated that the molecules adopt anti ‐folded conformations with folding dihedral angles of 44°/44° and 39°/41°, respectively. The crystal structure of anti ‐folded ( E )‐DMXA does not indicate any xanthenylium–anthracenolate push–pull effect. E, Z ‐diastereomerization of DMXA was studied by 1 H‐NMR coalescence‐temperature measurements at different magnetic field strengths and by kinetic equilibration experiments. Free energy of activation for this process was 81.5 (±1.3) kJ/mol. B3LYP/6‐311+G( d, p ) calculations showed that anti ‐folded conformers of XA, ( E )‐DMXA, bianthrone (AA), and dixanthylene (XX) were global minima. The twisted conformers of XA, AA, and XX were local minima (Δ G 298 = 16, 18, and 24 kJ/mol) with a substantial dipolar xanthenylium–anthracenolate dipolar contribution for XA. Chirality 27:919–928, 2015 . © 2015 Wiley Periodicals, Inc. Abstract :